Drama Appreciation as a Gateway to Empathy and Cultural Awareness in Schools - Andreas Simamora; Joseva Paschalina Hutabarat; Nur Syahfitri br. Sitepu; Melanie Theresia Pangaribuan (Faculty of Tarbiyah nad Teacher Training, 2026)
This research explores the ways in which drama appreciation can improve students’ empathy and cultural awareness within educational contexts. Employing a qualitative descriptive methodology, the study examines chosen conversations from The Comedy of Errors by William Shakespeare. The research emphasizes how misinterpretations and breaches of conversational maxims enable students to examine various viewpoints, feelings, and cultural backgrounds. The results indicate that drama offers significant learning opportunities that promote students' abilities to understand different perspectives and emotions. Furthermore, drama introduces students to various cultural norms and communication methods, enhancing their awareness of cultural variations. This research emphasizes the importance of drama as a powerful educational instrument by linking theoretical frameworks like pragmatics, emotional intelligence, and experiential learning with practical analysis. Consequently, it is suggested that drama appreciation serves as a method to enhance students' emotional and cultural growth in educational settings